The Broadview anthology of American literature. - Spires, Derrick Ramon (Tonawanda, NY, USA : Tonawanda, NY, USA : Broadview Press, 2022)
"About the Anthology Covering American literature from its pre-contact Indigenous beginnings through the Reconstruction period, the first two volumes of The Broadview Anthology of American Literature represent a substantial reconceiving of the canon of early American literature. Guided by the latest scholarship in American literary studies, and deeply committed to inclusiveness, social responsibility, and rigorous contextualization, the anthology balances representation of widely agreed-upon major works with an emphasis on American literature's diversity, variety, breadth, and connections with the rest of the Americas."--
Volume B. 1820 to Reconstruction / general editors: Derrick R. Spires, Cornell University Rachel Greenwald Smith, Saint Louis University Christina Roberts, Seattle University Joseph Rezek, Boston University Justine S. Murison, University of Illinois, Urbana-Champaign Laura L. Mielke, University of Kansas Christopher Looby, UCLA Rodrigo Lazo, UC Irvine Alisha Knight, Washington College Hsuan L. Hsu, UC Davis Michael Everton, Simon Fraser University Christine Bold, University of Guelph.
Includes bibliographical references and index.
Issued also in electronic format.
Keywords: American literature; American literature; Literature; Literature